Intermediate- and Deep-Water Oxygenation History in the Subarctic North Pacific During the Last Deglacial Period - Ovsepyan, Ekaterina; Ivanova, Elena; Tetard, Martin; Max, Lars; Tiedemann, Ralf (Frontiers in Earth Science, 2021)
Deglacial dissolved oxygen concentrations were semiquantitatively estimated for intermediate and deep waters in the western Bering Sea using the benthic foraminiferal-based transfer function developed by Tetard et al. (2017, 2021a). Benthic foraminiferal assemblages were analyzed from two sediment cores, SO201-2-85KL (963 m below sea level (mbsl), the intermediate-water core) and SO201-2-77KL (2163 mbsl, the deep-water core), collected from the Shirshov Ridge in the western Bering Sea. Intermediate waters were characterized by an oxygen content of ~2.0 ml L-1 or more during the Last Glacial Maximum (LGM)–Heinrich 1 (H1), around 0.15 ml L-1 during the middle Bølling/Allerød (B/A)–Early Holocene (EH), and a slight increase in [O2] (~0.20 ml L-1) at the beginning of the Younger Dryas (YD). Deep-water oxygen concentrations ranged from 0.9 to 2.5 ml L-1 during the LGM–H1, hovered around 0.08 ml L-1 at the onset of B/A, and were within the 0.30–0.85 ml L-1 range from the middle B/A to the first half of YD and the 1.0–1.7 ml L-1 range from the middle to late Holocene. The [O2] variations remind the δ18O NGRIP record thereby providing evidence for a link between the Bering Sea oxygenation at intermediate depths and the deglacial North Atlantic climate. Changes in the deep-water oxygen concentrations mostly resemble the deglacial dynamics of the Southern Ocean upwelling intensity which is supposed to be closely coupled with the Antarctic climate variability. This coherence suggests that deglacial [O2] variations were primarily controlled by changes in the circulation of southern-sourced waters. Nevertheless, the signal from the south at the deeper site might be amplified by the Northern Hemisphere climate warming via an increase in sea-surface bioproductivity during the B/A and EH. A semi-enclosed position of the Bering Sea and sea-level oscillations might significantly contribute to the magnitude of oxygenation changes in the study area during the last deglaciation. Interregional correlation of different proxy data from a wide range of water depths indicates that deglacial oxygenation changes were more pronounced in the Bering and Okhotsk marginal seas than along the open-ocean continental margin and abyssal settings of the North Pacific.